2009
DOI: 10.1007/s10577-009-9025-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure and chromosome distribution of three repetitive DNA families in Anemone hortensis L. (Ranunculaceae)

Abstract: The structure, abundance and location of repetitive DNA sequences on chromosomes can characterize the nature of higher plant genomes. Here we report on three new repeat DNA families isolated from Anemone hortensis L.; (i) AhTR1, a family of satellite DNA (stDNA) composed of a 554-561 bp long EcoRV monomer; (ii) AhTR2, a stDNA family composed of a 743 bp long HindIII monomer and; (iii) AhDR, a repeat family composed of a 945 bp long HindIII fragment that exhibits some sequence similarity to Ty3/gypsy-like retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…The co-location of retroelements with heterochromatic regions has been reported in other species, such as Anemone hortensis L. (Mlinarec et al 2009). …”
Section: In Fact This Probe Showed Successful Hybridization In Both mentioning
confidence: 61%
“…The co-location of retroelements with heterochromatic regions has been reported in other species, such as Anemone hortensis L. (Mlinarec et al 2009). …”
Section: In Fact This Probe Showed Successful Hybridization In Both mentioning
confidence: 61%
“…Furthermore, this study also showed a close relationship between A. apennina and A. blanda . Their affiliation was indicated in previous studies based on satellite DNA (Hagemann, Scheer & Schweizer, ; Mlinarec et al ., ). Hoot et al .…”
Section: Discussionmentioning
confidence: 97%
“…elliottii , P. densiflora Siebold & Zucc., P. taeda L. and P. sylvestris L. (Fuchs et al ., ; Hizume et al ., ; Schmidt et al ., ; Shibata, Matsusaki & Hizume, ; Islam‐Faridi et al ., ), with each chromosome usually displaying more than one signal (up to six). The Arabidopsis telomere motif TTTAGGG or its degenerate variants have previously been reported within tandem repeats, but could not be detected in interstitial positions by FISH using telomere‐specific probes (Mlinarec et al ., ).…”
Section: Discussionmentioning
confidence: 97%